1996
DOI: 10.1080/01652176.1996.9694614
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between atrial fibrillation and primary hypothyroidism in the dog

Abstract: Atrial fibrillation (AF) and primary hypothyroidism are most often diagnosed in middle-aged and older dogs of large and giant breeds. We hypothesized that the frequency of primary hypothyroidism may be higher in dogs with AF than in those without AF. Two groups were investigated. Group 1 (March 1987-June 1990) consisted of 128 dogs with AF. A thyroid-stimulating hormone (TSH) stimulation test was performed in dogs with a low voltage on the ECG and low uptake of pertechnetate on a thyroid scan. Group 2 (July 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The frequencies of primary hypothyroidism in AF dogs were significantly higher than in the control animals, suggesting hypothyroidism may contribute to AF. 27 Nevertheless, there are no prior experiments specifically designed to examine the effects of hypothyroidism on AF arrhythmogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of primary hypothyroidism in AF dogs were significantly higher than in the control animals, suggesting hypothyroidism may contribute to AF. 27 Nevertheless, there are no prior experiments specifically designed to examine the effects of hypothyroidism on AF arrhythmogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…25 Atrial fibrillation also has been associated with spontaneous canine hypothyroidism. 1,26 One of these studies suggested that atrial fibrillation might be associated with coronary atherosclerosis, 1 but the pathophysiology of cardiac dysfunction in canine hypothyroidism is likely multifactorial and is not well understood. 25 In the present study, 20 of 30 dogs with atherosclerosis had atherosclerosis of the coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation has been suggested to be associated with hypothyroidism in dogs (Gerritsen et al, 1996), but this appears to be rare based on findings in other studies (Panciera, 2001). Abnormalities identified on physical examination may include bradycardia and a weak apex beat.…”
Section: Cardiovascular Signsmentioning
confidence: 97%